2019
DOI: 10.1039/c8ta10735a
|View full text |Cite|
|
Sign up to set email alerts
|

Comment on “Bi-functional Li2B12H12 for energy storage and conversion applications: solid-state electrolyte and luminescent down-conversion dye” by J. A. Teprovich Jr, H. Colón-Mercado, A. L. Washington II, P. A. Ward, S. Greenway, D. M. Missimer, H. Hartman, J. Velten, J. H. Christian and R. Zidan, J. Mater. Chem. A, 2015, 3, 22853

Abstract: Assessment of metal closo-borane photoluminescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…For example, due to their large HOMO–LUMO gaps, unfunctionalized boron clusters (e.g., closo -[B 12 H 12 ] 2– ) remain photophysically inert. Therefore, they are energetically unlikely to engage in photoexcited charge-transfer or electron-transfer behavior induced by visible light, despite some recent mechanistic claims. , We note that identification of impurities and careful and complete spectroscopic characterization is always critical to ascertain the photophysical properties of any molecular and hybrid systems containing new boron cluster species. …”
Section: Discussionmentioning
confidence: 99%
“…For example, due to their large HOMO–LUMO gaps, unfunctionalized boron clusters (e.g., closo -[B 12 H 12 ] 2– ) remain photophysically inert. Therefore, they are energetically unlikely to engage in photoexcited charge-transfer or electron-transfer behavior induced by visible light, despite some recent mechanistic claims. , We note that identification of impurities and careful and complete spectroscopic characterization is always critical to ascertain the photophysical properties of any molecular and hybrid systems containing new boron cluster species. …”
Section: Discussionmentioning
confidence: 99%
“…A few perovskite-type metal borohydrides were investigated with respect to luminescent properties too, and it was found that CsEu(BH 4 ) 3 exhibits a 20 nm red shift compared to pristine Eu(BH 4 ) 2 [106]. Interestingly, closo-borates were also investigated regarding their photoluminescence, where ultraviolet emission was observable from Sc, Y, and La as well as Li, Na, and Eu-based B 10 H 10 2− and B 12 H 12 2− compounds, while visible light emission was postulated from arachno-borates [397].…”
Section: New Trends and Propertiesmentioning
confidence: 99%
“…Synthesis routes include wet chemistry [95,405] and especially mechano-chemistry [101,102,207,406], that can be easily scaled up, while structural investigations include the use of either x-ray or neutron diffraction and spectroscopies (e.g. Raman, NMR, FT-IR (Fourier transform infrared) etc) [158,228,[388][389][390][391][392][393][394][395][396][397][398].…”
Section: Outlooks and Conclusionmentioning
confidence: 99%
“…32,[101][102][103] Some of the closo-hydroborate anion mixtures can also be obtained by the reaction products from [BH4] − salts and neutral decaborane B10H14. 104,105 Recent studies show that anion mixtures of closo-hydroborates or monocarbaborates with an open-cage nido-hydroborate [B11H14] − stabilize a disordered phase and also exhibit high room-temperature ionic conductivity (>10 −3 S cm −1 ) respectively . [43][44][45]68,106 In principle, Na closo-hydroborates and monocarbaborates tend to exhibit roughly one-order-of-magnitude higher conductivity upon anion mixing than Li counterparts, 32,104,107 which can be attributed to the high polarizability and large ionic radius of Na + ions that are beneficial to cation conduction in the framework of the mixed closohydroborate anions.…”
Section: Discovery Of Superionic Conductorsmentioning
confidence: 99%